Impact of rainfall on spatio-temporal distribution of sediment organic matter along the Chittagong Coast, Bangladesh - Talukder, Avijit; Mallick, Debbrota; Mandal, Shamindra Nath; Anka, Ishrat Zahan; Shiuli, Milan Kumar; Hasin, Tasnuba; Sarker, Shubha (Research in Agriculture Livestock and Fisheries, 2016)
Sediment organic matter regulates the coastal biogeochemical cycle which is influenced by rainfall pattern and has potential relationship with organic carbon as well as mud characteristics. The objective of present research was to identify the impact of precipitation on the spatiotemporal variation inorganic features of intertidal mudflats. Three locations were selected in freshwater zone; two were in brackish water region and last three locations situated in marine waters from Halda to Salimpur coast. Two sites from each location were designated as the highest high tide level (onshore) and lowest low tide level (offshore) of the intertidal zone during winter (December to February) and monsoon (June to August) spanning between 2013 and 2014. Sediment organic matter and carbon were measured by combustion and Walkey-Black wet oxidation in turn. Average organic matter content in monsoon were found 4.5±0.03, 2.3±0.01 and 2.4 in freshwater, brackish and marine locations whereas 5.2±0.6, 3.9±0.14 and 5.4±0.04% investigated during winter. Precipitation pattern varies from different seasons and locations that have impact on land runoff, freshwater inflow, mixing and circulation. Mud dominated coastal intertidal zones represented high organic matter content than sand dominated coast. Furthermore, depositional pattern, transport, erosion-accretion processes, tidal action, wave characteristics and seasonal inconstancy control the organic matter characteristics in the coastal sediment. This research suggests the necessity of periodic observation of rainfall pattern and organic matter distribution to assess the intertidal deposits which support the stabilization of local geomorphology and biogeochemistry in Chittagong coastal region. Res. Agric., Livest. Fish.3(1): 175-186, April 2016